Menopause in women with schizophrenia, schizoaffective disorder and bipolar disorder. (October 2021) - Szeliga, Anna; Stefanowski, Bogdan; Meczekalski, Blazej; Snopek, Milena; Kostrzak, Anna; Smolarczyk, Roman; Bala, Gregory; Duszewska, Anna; Smolarczyk, Katarzyna; Maciejewska-Jeske, Marzena
Highlights: Menopausal symptoms may have a negative impact on the course of severe mental illness. Menopause is a risk factor for mood symptoms, but the evidence on the effect of menopause on new-onset severe mental illness is inconclusive. The prevalence of chronic disease is higher in women with severe mental illness than in the general population. The management of menopause in women with severe mental illness should take a multi-disciplinary approach. Abstract: The transition to menopause, usually occurring between the ages of 40 and 55, is a time when women are particularly vulnerable. When preexisting mental illness is present, symptoms are often amplified during this period. Moreover, women with mental illnesses experience menopausal symptoms similarly to healthy women. In this narrative review we summarize the current data regarding menopause in women with schizophrenia, schizoaffective disorder, and bipolar disorder, as well as current standards of management and care. The management of chronic disease in women suffering from severe mental illness is also considered.